RAD-Seq Analysis and in situ Monitoring of Nassau Grouper Reveal Fine-Scale Population Structure and Origins of Aggregating Fish - Sherman, Krista D.; Paris, Josephine R.; King, Robert Andrew; Moore, Karen A.; Dahlgren, Craig P.; Knowles, Lindy C.; Stump, Kristine; Tyler, Charles R.; Stevens, Jamie R. (Frontiers in Marine Science, 2020)
Nassau grouper (Epinephelus striatus) Bloch, 1792 are globally critically endangered and an important fishery species in The Commonwealth of The Bahamas (hereafter The Bahamas) and parts of the Caribbean, with an urgent need for better management and conservation. Here, we adopted a combined approach, integrating restriction-site-associated DNA sequencing (RAD-seq) and acoustic telemetry to establish country-wide demographic structure, diversity and connectivity, and the origins of Nassau grouper using an active fish spawning aggregation (FSA) in the central Bahamas. RAD-seq analysis of 94 Nassau grouper sampled from nine locations in The Bahamas generated a working dataset of 13,241 single nucleotide polymorphisms. Similar levels of genetic diversity were found among sampled locations. Evidence of population sub-structuring across The Bahamas was demonstrated and supported by discriminate analysis of principal components (DAPCs) along with analyses of molecular variance (AMOVAs). Associated acoustic telemetry data indicated Nassau grouper tagged at an active FSA in the central Bahamas during the 2016-2017 spawning season migrated to the Exumas at the conclusion of the spawning period. Telemetry data suggest the likely origins of five individuals, which travelled one-way distances of up to 176 km from the FSA in the central Bahamas to two sites within a no-take marine protected area (MPA). Analyses of high-resolution SNP markers (including candidate loci under selection) illustrated patterns of spatial structure and genetic connectivity not reflected by telemetry data alone. Nassau grouper from Exuma and Long Island appear to have genetic signatures that differ from other islands and from the Hail Mary FSA. Collectively, these findings provide novel information on the intraspecific population dynamics of Nassau grouper within The Bahamian archipelago and within an active FSA.